Addiction care in crisis: evidence should drive progressive policy and practice. (December 2019) - Bhui, Kamaldeep S.; Byrne, Peter; Goslar, Diane; Sinclair, Julia
Summary: Addictions are challenging health and social problems that need to be addressed to preserve and promote good mental health and ensure that individuals within society lead healthy and productive lives. Tackling addictions is complex and requires communities, public health, specialist services, and local and national government to act in unison and implement evidence-based interventions. This editorial raises systemic issues that need attention and proposes a range of systemic options.